Imatinib use for gastrointestinal stromal tumors among older patients in Japan and Taiwan - Yuichi Ichinose; Yi-Hsin Yang; Hui-Jen Tsai; Ru-Yu Huang; Takahiro Higashi; Toshirou Nishida; Li-Tzong Chen (Scientific Reports, 2022)
Abstract Tyrosine kinase inhibitors (TKIs) improve the prognosis of patients with gastrointestinal stromal tumors (GISTs). We conducted a retrospective cohort study using cancer registries linked with health utilization data in Japan and Taiwan to assess TKI usage in older and non-older patients. Patients diagnosed with GIST (2012–2014) were categorized into the following: adjuvant and advanced/metastatic settings. The duration and patterns of imatinib therapy were compared between the older (aged ≥ 75 years) and non-older (< 75 years) groups. We included 232 Japanese and 492 Taiwanese patients in the adjuvant setting, and 235 Japanese and 401 Taiwanese patients in the advanced/metastatic setting. Older patients had higher proportions of starting with lower doses (< 400 mg/day) than the non-older patients (adjuvant: 22.5% vs. 4.3% [Japan]; 22.5% vs. 10.9% [Taiwan]; advanced/metastatic: 29.6% vs. 7.2% [Japan]; 32.6% vs. 8.1% [Taiwan]; all p < 0.01). The median time to stop imatinib was shorter in the older than in the non-older patients (adjuvant: 301 vs. 975 days [Japan], 366 vs. 1028 days [Taiwan]; advanced/metastatic: 423 vs. 542 days [Japan]; 366.5 vs. 837 days [Taiwan]). More older patients with GIST tended to have TKIs at a lower initial dose and a shorter imatinib duration than the non-older patients.